Mission Mumbai : a novel of sacred cows, snakes, and stolen toilets - Narsimhan, Mahtab (Scholastic Press, 2016)
Dylan, an aspiring photographer, is spending a month in Mumbai with his friend Rohit Lal and his family, but knowing nothing of Indian culture, he cannot seem to do anything right (do not hit cows!)--and the situation is made worse by the tensions within the Lal family over whether Rohit should be raised in India, which Mr. Lal's wealthy sister is pushing for.